Critical Analysis of Emergency Medical Services in Disaster Response: Preparedness, Execution, and Challenges - ALYAMI, SALEH MOHAMMED AHMED; ALWAYILY, AHMED HMOOD; ALSHAMMARY, BANDAR HAMMAD NAHAR; ALMAKHALAS, ABDULHADI ALI; ALYAME, ADEL ATEF; ALGHAMDI, ABDULLAH HASAN SAEED; ALSHAMMARI, MESHAL SHAFAQ S; ALHAZYAH, SAEED ALI SALEM; ALSHAMMARI, FAYEZ DHABA NAIF; ALSHAMMARI, MOHAMMED FAHD (Journal of Ecohumanism, 2024)
EMS is an important link in the chain of disaster management and outlines the approach to emergency healthcare and the number of people saved during large-scale disasters. Here, the preparedness, implementation, and issues connected with EMS in regard to disasters will be critiqued in this paper. The current paper is an exploratory study that looks at how efficient EMS systems are in disaster areas: training, coordination, resource management, and technological integration through the review of literature and analysis of recent global disasters. The study indicates that although EMS is central to disaster management, factors like lack of resources, inadequate communication channels, and pressure on personnel limit the effectiveness of disaster response. Given this, the paper recommends improvement in the personnel training about technology as well as in the area of communication. Moreover, it suggests introducing psychological traumatization for the staff of the EMs and pledging for better apparatus. The outcomes presented here are written as recommendations that practitioners may use to enhance the functioning of EMS systems, increase organizational coherence, improve system cooperation, improve professional care, facilitate material coordination, and improve communication aid.